2014
DOI: 10.1007/s00441-014-2042-2
|View full text |Cite
|
Sign up to set email alerts
|

ATP promotes extracellular matrix biosynthesis of intervertebral disc cells

Abstract: A recent study by our lab found high accumulation of extracellular adenosine triphosphate (ATP) in the center of healthy porcine intervertebral discs (IVD). Since ATP is a powerful extracellular signaling molecule, extracellular ATP accumulation may regulate biological activities in the IVD. Therefore, the objective of this study was to investigate the effects of extracellular ATP on the extracellular matrix (ECM) biosynthesis of porcine IVD cells isolated from two distinct anatomical regions: annulus fibrosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…We previously found a high extracellular accumulation of ATP at approximately 165 μM in the NP region [Wang et al, 2013], while 100 μM of extracellular ATP could effectively promote IVD cell ECM synthesis [Gonzales et al, 2015]. Since ATP is often rapidly hydrolyzed into adenosine by ectonucleotidases, a similar level (100 μM) of extracellular adenosine accumulation could be expected.…”
Section: Pg and Collagen Protein Measurementsmentioning
confidence: 86%
See 3 more Smart Citations
“…We previously found a high extracellular accumulation of ATP at approximately 165 μM in the NP region [Wang et al, 2013], while 100 μM of extracellular ATP could effectively promote IVD cell ECM synthesis [Gonzales et al, 2015]. Since ATP is often rapidly hydrolyzed into adenosine by ectonucleotidases, a similar level (100 μM) of extracellular adenosine accumulation could be expected.…”
Section: Pg and Collagen Protein Measurementsmentioning
confidence: 86%
“…The cell-agarose constructs (8 mm in diameter and 2 mm thick) were made by mixing equal volumes of 2 × 10 7 cells/mL cell suspension and 4% agarose (Sigma-Aldrich) gel solution, and casting 100 µL of the mixture into individual wells of a custom designed mold. Therefore, the final concentration in each sample is 10 7 cells/mL in 2% agarose [Gonzales et al, 2015], which was then cultured at 37 ° C, 5% CO 2 in DMEM supplemented with 10% FBS and 1% antibiotic-antimycotic for 2 days before the experiment.…”
Section: Ivd Cells Isolation and Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Garcia and Knight suggested putative mechanism of ATP release via hemichannels (formed of connexin-43 subunits) in response to cyclic compression [131]. Since then a number of studies has shown that exogenous ATP supplementation, even in the absence of mechanical stimulation, can promote ECM biosynthesis and accumulation providing energy supply to fuel that process [132], increase mechanical properties, particularly through structural organization of the bulk phase and territorial ECM [133]. Exogenous ATP effects are proven to be dose-and time-dependent, where high doses can promote catabolic responses, necessitating the optimization of therapeutic dose range and application timing (e.g., transient vs. continuous) to the cell type and culture system [133][134][135].…”
Section: Purinergic Signalingmentioning
confidence: 99%